Rapid screening of destruxins by liquid chromatography/mass spectrometry - Jegorov, A; Havlícek, V; Sedmera, P (Journal of mass spectrometry, 1998)
A liquid chromatographic/mass spectrometric (LC/MS) method utilizing an atmospheric pressure chemical ionization (APCI) interface and in-source collisionally induced dissociation (CID) was developed for the rapid screening of the cyclic hexadepsipeptides destruxins, produced by the fungi Metarhizium anisopliae and Trichothecium roseum. The APCI mass spectra are fully consistent with the high-energy CID data but the sequence ions are abundant over the whole mass range. In addition to 22 known destruxins, two new representatives of this family were detected by LC/MS analysis: destruxin Ed1 and roseotoxin A were isolated and their structures were inferred from MS/MS and NMR data.
Keywords: Chromatography, High Pressure Liquid; spektrometrie hmotnostní - bombardování rychlými atomy; Spectrometry, Mass, Fast Atom Bombardment; Chromatography, Liquid; mitosporické houby; Spectrophotometry, Ultraviolet; Mitosporic Fungi; hmotnostní spektrometrie; cyklické peptidy; spektrofotometrie ultrafialová; Mass Spectrometry; Peptides, Cyclic; chromatografie kapalinová; vysokoúčinná kapalinová chromatografie